Studi Analisis Wisata Halal Pacuan Kuda Sumbawa: Potensi dan Strategi Peningkatan Ekonomi Kreatif Masyarakat Lokal - Ardiansyah, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the potential integration between the traditional Sumbawa horse racing tradition (Maen Jaran) and the concept of halal tourism as an innovative strategy to enhance the creative economy of the local community. Using a descriptive qualitative approach, this study explores how local cultural values can be synergized with global halal service standards. The findings indicate that Sumbawa horse racing has a significant unique appeal, yet its development is still constrained by limited halal infrastructure and human resource capacity. This article formulates strategies for the development of integrated tourism products, strengthening halal certification in the MSME sector, and utilizing digital technology to expand market reach. The implications of this study provide guidance for stakeholders in realizing sustainable tourism based on local wisdom and Sharia principles.